Developmental Flows and Agricultural Output in Nigeria - Ebenezer, Ariyibi Mayowa; Olubukola, Sunmonu Sadiat; Taofeek Osidero , Agbatogun (The Journal of Accounting and Management, 2025)
The challenge of the agricultural sector in Nigeria and most developing countries has been inadequate and improper funding, which has stifled the reducing of poverty and hunger in most African countries Nigeria Inclusive. Based on this issue this inquiry examines into the influence of developmental flows on agricultural output in Nigeria. The secondary data was sourced from the Food and Agriculture Statistics of the United Nation Organization, for the period of 1991 to 2023. The study employed the Auto-regressive Distributed Lag Length to determine the short and long-run relationship between the outcome variable and independent variable. The findings reveals that Credit to agriculture and Multi-lateral donor has positive significant effect on Agricultural output while foreign direct investment in agriculture has a negative significant effect on Agricultural output. These findings suggest that the effectiveness of funding mechanisms depends on alignment with local needs, efficient resource utilization, and appropriate policy frameworks. Policymakers must focus on enhancing credit accessibility to support farmers directly, as it demonstrates the most consistent positive impact on agricultural output. It therefore recommended that government should investigate the structural and operational barriers limiting the positive impact of FDI on agricultural productivity in Nigeria.